Bloodlines - Correia, Larry (Riverdale, NY Baen, 2021)
"The chaos god Asag has been quiet since the destruction of the City of Monsters, but Monster Hunter International know that he is still out there, somewhere-plotting, waiting for his chance to unravel reality. When Owen and the MHI team discover that one of Isaac Newton's Ward Stones is being auctioned off by Reptoids who live deep beneath Atlanta, they decide to steal the magical super weapon and use it to destroy Asag once and for all. But before the stone can be handed off, it is stolen by a mysterious thief with ties to MHI and the Vatican's Secret Guard. It's a race against time, the Secret Guard, a spectral bounty hunter, and a whole bunch of monsters to acquire the Ward Stone and use it against Asag. For as dangerous as the chaos god is, there is something much older-and infinitely more evil-awakening deep in the jungles of South America"--
113826
Keywords: Monsters -- Fiction; Hunters -- Fiction; Thieves -- Fiction; Magic -- Fiction; Fantasy fiction; Fiction